High-speed photo detection at two-micron-wavelength : technology enablement by GeSn/Ge multiple-quantum-well photodiode on 300 mm Si substrate - Xu, Shengqiang (2019)
We report high-speed photo detection at two-micron-wavelength achieved by a GeSn/Ge multiple-quantum-well (MQW) p-i-n photodiode, exhibiting a 3-dB bandwidth (f3-dB) above 10 GHz for the first time. The epitaxy of device layer stacks was performed on a standard (001)-oriented 300 mm Si substrate by using reduced pressure chemical vapor deposition (RPCVD). The results showed promise for large-scale manufacturing. To our knowledge, this is also the first photodiodes-on-Si with direct radio-frequency (RF) measurement to quantitatively confirm high-speed functionality with tens of GHz f3-dB at 2 µm, which is considered as a promising candidate for the next data communication window. This work illustrates the potential for using GeSn to extend the utility of Si photonics in 2 µm band integrated optical transceivers for communication applications.